Foreign bank entry, credit allocation and lending rates in emerging markets: Empirical evidence from Poland - Degryse, Hans; Havrylchyk, Olena; Jurzyk, Emilia; Kozak, Sylwester (Journal of Banking & Finance, 2012)
Earlier studies have documented that foreign banks charge lower lending rates and interest spreads than domestic banks. We hypothesize that this may stem from the superior efficiency of foreign entrants that they decide to pass onto borrowers (“performance hypothesis”), but could also reflect a different loan allocation with respect to borrower transparency, loan maturity and currency (“portfolio composition hypothesis”). We are able to differentiate between the above hypotheses thanks to a novel dataset containing detailed bank-specific information for the Polish banking industry. Our findings demonstrate that banks differ significantly in terms of portfolio composition and we attest to the “portfolio composition hypothesis” by showing that, having controlled for portfolio composition, there are no differences in lending rates between banks.